This is EPIC: Extensive Periphery for Impact and Control to study seabird habitat loss in and around offshore wind farms combining a peripheral control area and Bayesian statistics - Anne Grundlehner; Mardik F. Leopold; Anna Kersten (Ecological Informatics)
With the rapidly increasing intensity of human activities in the marine realm, it has become urgent to better understand the impacts of human-induced disturbances on marine species. Marine mammals and birds are often observed to alter their fine-scale spatial distribution patterns in the presence of human at-sea activities, such as ship traffic and offshore wind farms (OWFs). This study presents EPIC (Extensive Periphery for Impact and Control), a novel approach for investigating such displacement in marine megafauna. The approach consists of a survey design that uses the OWFs surroundings in all directions as control space, complemented by a sophisticated statistical approach to quantify the extent and intensity of displacement and habitat loss in and around the area of potential disturbance. The approach is showcased by investigating the effects of an OWF in the Dutch North Sea on the habitat use of razorbills (Alca torda) and common guillemots (Uria aalge), two seabird species that occur in large numbers across the North Sea. We used an explicit spatial-temporal Bayesian model to predict their spatial distribution patterns based on eight aerial surveysed. The model output is used for a simulation study, comparing bird densities in the potential impact area with 1000 similarly sized control areas from the peripheral control space and from these, displacement around the OWF. Strong displacement was found for both razorbills and guillemots, within the OWF footprint but also in its surroundings. Razorbill and guillemot densities inside the OWF were reduced by 0.953 and 1.604 individuals per km2, respectively, compared to the remainder of the study area, remaining considerably lower than control densities up to 2 km and > 10 km distance. The presented methodological approach holds great potential for future studies on the effects of local disturbances on displacement of marine megafauna.